THE IMPLEMENTATION OF BUTON CULTURAL VALUES IN VALUE EDUCATION PLANNING IN BAUBAU REGION OF SOUTHEAST SULAWESI - Hindaryatiningsih, Nanik (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The study aimed at finding out the implementation of Buton cultural value into value education planning. This study employed qualitative approach by ethnographic method conducted at SMAN 2 Baubau, south east Sulawesi in 2012. For data collection, in-depth interview techniques, documentation review, and participant observation consisting descriptive, focused and selected observation were used. The observation focused on cultural events and interactive behavioral informants. The informants comprised of principal, teachers, staff, school committee, pupils, parents, community leaders and traditional leaders. For data analysis, spradley technique consisting of domain analysis, taxonomy, componential and theme analysis was used. The findings showed that 1) core values in â€œgau and pombalaâ€ culture in Buton community consisted of cooperative, democratic and ethic value; 2) Butonâ€™s cultural values ofâ€œgau and pombalaâ€™ were practiced in educational value planning at school. Keywords: democratic, cooperative, ethic, value implementation, educational planning